Clinical presentation and management practice of systemic mastocytosis. A survey on 460 Italian patients. Issue 7 (2nd June 2016) - Pieri, Lisa; Bonadonna, Patrizia; Elena, Chiara; Papayannidis, Cristina; Grifoni, Federica Irene; Rondoni, Michela; Girlanda, Stefania; Mauro, Marina; Magliacane, Diomira; Elli, Elena Maria; Iorno, Maria Loredana; Almerigogna, Fabio; et al.
Abstract : Systemic mastocytosis is a rare heterogeneous myeloproliferative neoplasm characterized by abnormal proliferation and activation of mast cells. We describe a large multicentre series of 460 adult patients with systemic mastocytosis, with a diagnosis based on WHO 2008 criteria, in a "real‐life" setting of ten Italian centers with dedicated multidisciplinary programs. We included indolent forms with ( n  = 255) and without ( n  = 165) skin lesions, smouldering ( n  = 20), aggressive ( n  = 28), associated with other hematological diseases mastocytosis ( n  = 21) and mast cell leukemia ( n  = 1). This series was uniquely characterized by a substantial proportion of patients with low burden of neoplastic mast cells; notably, 38% of cases were diagnosed using only minor diagnostic criteria according to WHO 2008 classification, underlying the feasibility of early diagnosis where all diagnostic approaches are made available. This has particular clinical relevance for prevention of anaphylaxis manifestations, that were typically associated with indolent forms. In multivariate analysis, the most important features associated with shortened overall survival were disease subtype and age at diagnosis >60 years. Disease progression was correlated with mastocytosis subtype and thrombocytopenia. As many as 32% of patients with aggressive mastocytosis suffered from early evolution into acute leukemia. Overall, this study provides novel information about diagnostic approaches and current presentation of patients with SM and underlines the importance of networks and specialized centers to facilitate early diagnosis and prevent disease‐associated manifestations. Am. J. Hematol. 91:692–699, 2016. © 2016 Wiley Periodicals, Inc.